Novel synthesis of high surface area nano-CeZrO2: transformation of the microstructure and textural properties as the effect of calcination - Hadi, Abdul; Shah, M. Nazri Abu; Ismail, Kamariah Noor; Ismail, Roslina (IOP Publishing, 2018)
Semi-crystalline and crystalline ceria-zirconia, Ce 0.8 Zr 0.2 O 2 nanoparticles had been successfully synthesized by water/oil microemulsion method at room temperature without and with calcination process. The basic understanding on the influence of microemulsion system and the relation of calcination process on the microstructure of nanoparticles was studied. Without calcination, the semi-crystalline nanoparticles with the size in the range of <10 nm were produced. This size was consistent to the droplet size of microemulsion and the XRD crystallite size. In CeZrO 2 , zirconia ions incorporated into the ceria structure to form a complete solid solution of nanoparticles. The specific surface area was 169.80m 2 × g ?1 and it was found as a highly microporous material. While, after calcination process, the degree of crystallinity of nanoparticles increased and the fully crystalline nanoparticles were produced. The crystals and particles size grew up to 12 nm, while the surface area reduced to 46.59m 2 × g ?1 . However, both nanoparticles, with and without calcination, were consistent as a cubic structure. By comparing the properties of both nanoparticles samples, it can be concluded that the nanoparticles CeZrO 2 are able to be synthesized using the microemulsion method at room temperature without calcination process and it is suitable for catalysts application.